A diverse array of optical solitons of generalized nonlinear dispersive mK(m,n) model - Seadway, Aly R.; Ali, Asghar; Bekir, Ahmet; Cevikel, Adem C.; Alp, Murat (WORLD SCIENTIFIC PUBL CO PTE LTD, 2025)
The generalized mK(m,n) model is used to portray the movement of nonlinear waves by applying four mathematical methods with assistance of Mathematica software. These methods are called enhanced simple equation (SE) method, Exp(-Psi(xi))-expansion method, (G '/G)-expansion method and modified F-expansion method. For physical behavior, few solutions are plotted graphically in the form of two-dimensional (2D) and three-dimensional (3D). The techniques and soliton solutions that are developed provide computational tools for additional research in this area. With this work, we have gained a better knowledge of soliton motion and how it is used in dynamical systems and other related technologies. Hence, this work will help physicists envision some new ideas and hypotheses in nonlinear science.
Keywords: mathematical schemes; soliton solutions; mK(m; n)model; TRAVELING-WAVE SOLUTIONS; BIREFRINGENT FIBERS; EQUATIONS; Physics